Analisis Perbedaan Rata-Rata Indeks Pemberdayaan Gender di Jawa Timur - Khaerun Nisa (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2019)
This paper examines the average difference test of the gender empowerment index in the City / Regency in East Java Province in the period 2010-2015. This study aims to be used as a reference for the relevant government in East Java Province to detect cities / regencies that have a low gender empowerment index value and identify forming indicators that are the cause of the low value of the gender empowerment index in the area. The results of this study indicate that the development of the gender empowerment index in the City / Regency in East Java Province in the period 2010-2015 has improved. This indicates that the achievement of the role of women in politics and the economy and in making decisions from time to time is getting better. Although it cannot be denied that there are still gaps between the male and female population in the City / Regency in East Java.